How to raise an elephant [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2020)
As the temperature rises in Gaborone, Precious Ramotswe, founder of the No. 1 Ladies' Detective Agency, wonders whether the heat could be the reason that business is particularly slow. But then a distant cousin of Mma Ramotswe's comes to the agency with a plea for help and the ladies decide to pursue the issue together. Armed with Mma Ramotswe's circumspection and Mma Makutsi's sharp eye, they proceed with confidence and open hearts. What, after all, could be more straightforward than a family matter? Meanwhile, their colleague Charlie is behaving oddly, borrowing Mma Ramotswe's van and returning it in an unusual condition. Digging a little deeper, the explanation is both strange and extraordinary, and takes Charlie, along with Mma Ramotswe's husband, Mr J. L. B. Matekoni, on a hair-raising night-time expedition. In the end, Precious is reminded of the need to view a picture from every angle, to accept the imperfections in people and situations and then find a solution - preferably over a delicious slice of her friend Mma Potokwani's fruit cake.